2007
DOI: 10.1038/sj.jcbfm.9600504
|View full text |Cite
|
Sign up to set email alerts
|

Perfusion Magnetic Resonance Imaging Correlates of Neuropsychological Impairment in Multiple Sclerosis

Abstract: Although cognitive impairment is common in multiple sclerosis (MS), its pathophysiology is still poorly understood. Abnormalities of cerebral blood flow (CBF) have long been acknowledged in MS and advances in perfusion magnetic resonance imaging (MRI) allow for their assessment in vivo. We investigated the relationship between regional perfusion changes and neuropsychological (NP) dysfunctions in patients with relapsing-remitting and primary-progressive MS. Absolute CBF, cerebral blood volume (CBV) and mean tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
77
2
3

Year Published

2007
2007
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 39 publications
8
77
2
3
Order By: Relevance
“…25 While we did not corroborate their results in terms of our anterior and posterior basal ganglia regions, that study did not examine cortical GM, so there is no basis for comparison with respect to our frontal lobe findings. Paulesu et al 26 examined cerebral metabolic rates in patients with MS with memory impairment using PET imaging and identified significantly diminished metabolism in their bilateral prefrontal cortices compared with patients with MS without memory impairment.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…25 While we did not corroborate their results in terms of our anterior and posterior basal ganglia regions, that study did not examine cortical GM, so there is no basis for comparison with respect to our frontal lobe findings. Paulesu et al 26 examined cerebral metabolic rates in patients with MS with memory impairment using PET imaging and identified significantly diminished metabolism in their bilateral prefrontal cortices compared with patients with MS without memory impairment.…”
Section: Discussioncontrasting
confidence: 52%
“…There has been a single prior study that examined cerebral perfusion in cognitively impaired patients with MS. 25 Inglese et al reported significant correlations between subcortical GM CBF and the Rey Complex Figure Test score, and subcortical GM CBV and the Delis-Kaplan Executive Function System score. 25 While we did not corroborate their results in terms of our anterior and posterior basal ganglia regions, that study did not examine cortical GM, so there is no basis for comparison with respect to our frontal lobe findings.…”
Section: Discussionmentioning
confidence: 99%
“…15,35,36 The differences may be due to patient selection. Patients in our study all had relapsing-remitting MS with a higher median EDSS with similar disease duration compared with studies where a reduction in CBF was reported.…”
Section: Comparisons With Other Studiesmentioning
confidence: 99%
“…A comparação dos resultados relativos à Figura Complexa de Rey-Osterrieth, com outros estudos não foi possível, por diferença de metodologia empregada. A maioria das pesquisas utilizando esse teste era tipo caso-controle, não informava o percentual de pacientes com EM e comprometimento de memória de trabalho ou de curto prazo e tinha análise estatística por regressão multivariada ou correlação (Inglese et al, 2008;Schulz et al, 2006). O percentual de perda de memória de curto prazo avaliada pelo teste RAVLT igual a 17,8% desta pesquisa foi menor que os 33% referidos por Schulz et al (2006), usando o mesmo teste, embora se deva considerar que o padrão não foi construído para a população brasileira.…”
Section: Discussionunclassified
“…Ressaltaram que a perda de memó-ria de curto prazo deve ser valorizada no tratamento da EM, porque compromete muito o desempenho das ativi-dades diárias e reduz a qualidade de vida. Inglese et al (2008), também empregando esse instrumento, informaram que 50% dos pacientes tinham perda de memória de curto prazo. O percentual de pacientes da presente pesquisa com prejuízo dessa memória, avaliada pelo RAVLT, foi menor que os 33,3% relatados por Negreiros et al (2008), testando 54 pacientes na forma clínica surto-remissão, mas teve em comum a identificação de uma curva de aprendizagem que não se associou à gravidade de esclerose múltipla, avaliada pelo EDSS.…”
Section: Discussionunclassified